Fibre intake and the development of inflammatory bowel disease: A European prospective multi-centre cohort study (EPIC-IBD). (7th October 2017) - Andersen, Vibeke; Chan, Simon; Luben, Robert; Khaw, Kay-Tee; Olsen, Anja; Tjonneland, Anne; Kaaks, R; Grip, Olof; Bergmann, M M; Boeing, H; Hultdin, Johan; Karling, Pontus; et al.
Abstract: Background and Aims: Population-based prospective cohort studies investigating fibre intake and development of inflammatory bowel disease are lacking. Our aim was to investigate the association between fibre intake and the development of Crohn's disease [CD] and ulcerative colitis [UC] in a large European population. Methods: In total, 401326 participants, aged 20–80 years, were recruited in eight countries in Europe between 1991 and 1998. At baseline, fibre intake [total fibres, fibres from fruit, vegetables and cereals] was recorded using food frequency questionnaires. The cohort was monitored for the development of inflammatory bowel disease. Each case was matched with four controls and odds ratios [ORs] for the exposures were calculated using conditional logistic regression. Sensitivity analyses according to smoking status were computed. Results: In total, 104 and 221 participants developed incident CD and UC, respectively. For both CD and UC, there were no statistically significant associations with either quartiles, or trends across quartiles, for total fibre or any of the individual sources. The associations were not affected by adjusting for smoking and energy intake. Stratification according to smoking status showed null findings apart from an inverse association with cereal fibre and CD in non-smokers [Quartile 4 vs 1 OR = 0.12, 95% confidence interval = 0.02–0.75, p = 0.023, OR trend across quartiles = 0.50, 95% confidence interval = 0.29–0.86, p = 0.017]. Conclusion: The results do not support the hypothesis that dietary fibre is involved in the aetiology of UC, although future work should investigate whether there may be a protective effect of specific types of fibre according to smoking status in CD.